Influence of micromixing time and shear rate in fast contacting mixers on the precipitation of boehmite and NH4-dawsonite. (16th January 2018) - Lafficher, Robin; Digne, Mathieu; Salvatori, Fabien; Boualleg, Malika; Colson, Didier; Puel, François
Highlights: Boehmite and NH4 -dawsonite were precipitated in fast contacting mixers. Micromixing time range of 1–200 ms was achieved with fast contacting mixers. Micromixing time had no influence on boehmite crystallite size and properties. NH4 -dawsonite porosity was easily tuned with the operating conditions. Abstract: The textural properties of γ-alumina catalyst supports largely depend on the solid properties of their precursors. Precipitation in fast contacting mixers of two precursors, boehmite and NH4 -dawsonite, were investigated in order to obtain different and enhanced solid features. The mixing devices, a sliding surface mixing device (SSMD) and a rotor-stator mixer (RSM), were operated continuously. Micromixing was characterized by using a competitive parallel reaction system (iodide-iodate). It was possible to achieve micromixing time from 1 to 200 ms according to the type of mixer and the operating conditions. The micromixing times assessed experimentally are in correct agreement with the theoretical ones. For boehmite precursor, the micromixing time had not a decisive influence on the crystallite size. Better control of the particle surface area was obtained considering the shear rate level, maybe due to a disordered aggregation. Conversely, reduction of the crystallite size with a decrease of the micromixing time was observed with NH4 -dawsonite. A possible explanation lies in a higher local supersaturation, leading to a more intense primary nucleation. Moreover, it was possible to adjust the pore volume of the NH4 -dawsonite's aggregates with the operating conditions to quite a large extent (0.2 up to 0.8 cm 3 g –1 ).